2011
DOI: 10.1016/j.regpep.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic antagonism of ghrelin receptors attenuates development of nicotine induced locomotor sensitization in rats

Abstract: Aims Ghrelin (GHR) is an orexigenic gut peptide that interacts with ghrelin receptors (GHR-Rs) to modulate brain reinforcement circuits. Systemic GHR infusions augment cocaine stimulated locomotion and conditioned place preference (CPP) in rats, whereas genetic or pharmacological ablation of GHR-Rs has been shown to attenuate the acute locomotor-enhancing effects of nicotine, cocaine, amphetamine and alcohol and to blunt the CPP induced by food, alcohol, amphetamine and cocaine in mice. The stimulant nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 51 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…Ghrelin receptors have been localized on neurons within the ventral tegmental area (Guan et al, 1997; Abizaid, 2009), which in turn project via the mesolimbic dopamine (DA) pathway to multiple brain regions including the nucleus accumbens (NACc), the amygdala, prefrontal cortex and hippocampus (Fields et al, 2007). Modulation of the mesolimbic dopamine system by ghrelin is likely involved in the capacity of ghrelin to elicit eating and food-related reinforcement (Dickson et al, 2011; Egecioglu et al, 2011; Skibicka and Dickson, 2011) and also plays a key role in the behavioral activating and reward/reinforcement properties of drugs of abuse such as cocaine and nicotine (Jerlhag et al, 2010; Dickson et al, 2011; Wellman et al, 2011, 2012). Finally, ghrelin receptors located on cells of the PVN may play a key role in activation of the hypothalamic-pituitary-adrenal (HPA) axis (Asakawa et al, 2001; Patterson et al, 2010; Cabral et al, 2012), which suggests a role for ghrelin in stress.…”
Section: Ghrelin and Ghrelin Receptorsmentioning
confidence: 99%
“…Ghrelin receptors have been localized on neurons within the ventral tegmental area (Guan et al, 1997; Abizaid, 2009), which in turn project via the mesolimbic dopamine (DA) pathway to multiple brain regions including the nucleus accumbens (NACc), the amygdala, prefrontal cortex and hippocampus (Fields et al, 2007). Modulation of the mesolimbic dopamine system by ghrelin is likely involved in the capacity of ghrelin to elicit eating and food-related reinforcement (Dickson et al, 2011; Egecioglu et al, 2011; Skibicka and Dickson, 2011) and also plays a key role in the behavioral activating and reward/reinforcement properties of drugs of abuse such as cocaine and nicotine (Jerlhag et al, 2010; Dickson et al, 2011; Wellman et al, 2011, 2012). Finally, ghrelin receptors located on cells of the PVN may play a key role in activation of the hypothalamic-pituitary-adrenal (HPA) axis (Asakawa et al, 2001; Patterson et al, 2010; Cabral et al, 2012), which suggests a role for ghrelin in stress.…”
Section: Ghrelin and Ghrelin Receptorsmentioning
confidence: 99%
“…Using animal models, studies have shown that administration of ghrelin can increase ethanol intake, while ghrelin antagonism reduces ethanol intake (Jerlhag et al, 2009). In addition, ghrelin antagonists have been shown to significantly reduce the behavioral and physiological effects of cocaine (Clifford et al, 2012), amphetamine (Jerlhag et al, 2010), and nicotine (Wellman et al, 2011; Jerlhag and Engel, 2011). In agreement with pharmacological studies, GHSR knockout mice show reduced voluntary ethanol intake and diminished ethanol-induced conditioned place preference (Jerlhag et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years there has been mounting evidence that ghrelin is related to psychostimulant drug addiction [30][31][32][33] . In addition, ghrelin interacts with CART (Cocaine-and Amphetamine Regulated Transcript) peptides, which are known to be important in psychostimulant addiction / rewarding / reinforcing mechanisms [81][82][83] .…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is also involved in more complex cognitive-behavioral processes like learning, memory, reward, addiction and depressive and anxious symptoms 14,29 . In addition, it has been suggested that ghrelin (by a mechanism similar to compensatory increase to food restriction) could be important in drug, stimulant and alcohol abuseaddiction mechanisms [30][31][32][33] . As a result, it is important to design studies to investigate possible interactions between methylphenidate and ghrelin because ADHD increases the risk of drug and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%